Assessment of the Factors That Can Predict the Occurrence of Diabetic Ketoacidosis in Type 1 Diabetic Patients - Abdul Rashid Dayo, Shafi Muhammad Wassan, Qurrat Ul Ain Shahid, Abdul Hafeez Soomro, Niaz Ahmed, Mona Humaira (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Diabetes ketoacidosis (DKA) is a common acute complication seen in patients with diabetes mellitus (DM) type 1. It is avoidable by following a good management plan. The risk factors that have been previously identified for DKA are female gender, age, illiteracy, low socio-economic status, infection, poor metabolism, psychological issues, and poor compliance with the treatment. Objective: The present study aims at the determination of age, gender, socio-economic status, DKA at the time of initial diagnosis of DM type 1, parental education regarding the disease, psychological issues, infection, metabolic control, and poor compliance with insulin treatment as the predictive factors of DKA occurrence. Study design: A retrospective cohort study Place and Duration: This study was conducted at GMMC Teaching Hospital Sukkur from November 2021 to November 2022 Methodology: The present study was conducted by using the medical records of patients with DM type 1. The mean age of the patients was 18.2±5.31 with a range of 0-21 years. The data were assessed for the predictive factors of DKA. The dependent variable in the study was DKA occurrence. The independent variables were, compliance with the treatment with insulin, DM type 1, age, infection, psychological issues, metabolic control, parental education, socio-economic status, and diagnosis of DM type 1 on a DKA attack. Logistic regression analysis was done the determination the factors that seemed to increase the incidence of DKA. Results: A total of 42 patients with DM type 1 were included in the study. The incidence of DKA was 27 (64.29%) and 4 (9.52%) of these patients died. Multivariate analysis showed that infection and diagnosis of DM type 1 at the time of DKA were the most significant predictive factors for DKA. Conclusion: Diagnosis of DM type 1 at the time of DKA and infection are the most important factors for increasing the incidence of DKA. Keywords: Diabetic ketoacidosis, type 1 diabetes mellitus, infection, predictive factors